If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(v + -1) = 6 Reorder the terms: 6(-1 + v) = 6 (-1 * 6 + v * 6) = 6 (-6 + 6v) = 6 Solving -6 + 6v = 6 Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 6v = 6 + 6 Combine like terms: -6 + 6 = 0 0 + 6v = 6 + 6 6v = 6 + 6 Combine like terms: 6 + 6 = 12 6v = 12 Divide each side by '6'. v = 2 Simplifying v = 2
| x^2-10xy+6y^2-12=0 | | (x+2)(2x^2-3x+5)= | | (3x+10)=62 | | -6.7(4p+6)-1.7(3p-5)= | | 5x+1=6x-(3x-9) | | 5-2m=-19 | | 6-4c=2/3-1 | | =300-40Y | | 6x^2-6x-3=-1 | | (5x+9)=89 | | -7/2(y-6)-1/4y= | | f(x)=x(x-11) | | 2(w+6)-4w= | | 3(6x+1)=8(5x-10) | | 3^x=1/9 | | -92+42= | | 6x^2-4x-2=-1 | | 9x-9=2+2(x+2) | | (2/x-5)-5(x-5) | | sin24=7/x | | cosx+2cos^2x=0 | | Y=12(1.05)y | | 100[0.06(q+10)]= | | 50x+80(10)=60(x+10) | | 5.7x-5=4.7x | | 14x^2=21 | | x+2(x+1)+x^2= | | 28x^2=15x | | 8+4y=9-2x+6 | | 15x-8=3x+2-(x+5) | | 3cos^2x+sinx=1 | | -3000(ln/.20) |